FeMoO4-graphene oxide photo-electro-catalyst for berberine removal and hydrogen evolution. (26th July 2019) - Tang, Lina; Liu, Lifen; Yang, Fenglin
Abstract: Photo-electro-catalytic degradation of antibiotics such as berberine in water with simultaneous hydrogen evolution is an attractive option. It can control pollution using solar energy and provide clean energy. The photo electrodes play vital role in this kind of photocatalytic electrolytic cell. To obtain better electrode with high degradation capacity and fast hydrogen generation rate, using a facile one-pot hydrothermal process, a series of nano-structured composite FeMoO4 -GO (graphene oxide) catalysts with improved absorbance in 250–800 nm were synthesized, and loaded on CFC (carbon fiber cloth). Their photo electrode performance were compared. Using SEM(scanning electron microscope), XRD (X-ray diffraction) and XPS(X-ray photoelectron spectroscopy), the catalysts were characterized, and LSV(linear sweep voltammetry), CV(cyclic voltammetry) and EIS(electrochemical impedance) were used to characterize the electrodes. In 1 M KCl supporting electrolyte, at current density 10 mA cm −2, 90% berberine was removed in 30 min and hydrogen generation rate was 3.1 μmol cm −2 min −1 in photo-electro-catalysis system. The results show rapid hydrogen generation and enhanced pollutant degradation. Graphical abstract: Image 1 Highlights: FeMoO4 -GO/CFC were synthesized by a facile one-pot hydrothermal process. In PEC, FeMoO4 -GO/CFC was used as photo cathode. The catalyst benefits more for berberine removal and hydrogen evolution.